Association and expression of the antigen‐processing gene PSMB8, coding for low‐molecular‐mass protease 7, with vitiligo in North India: case–control study. (9th October 2017) - Dani, P.; Patnaik, N.; Singh, A.; Jaiswal, A.; Agrawal, B.; Kumar, A.A.; Varkhande, S.R.; Sharma, A.; Vaish, U.; Ghosh, P.; Sharma, V.K.; Sharma, P.; et al.
Summary: Background: Vitiligo is a multifactorial, autoimmune, depigmenting disorder of the skin where aberrant presentation of autoantigens may have a role. Objectives: To study the association of two antigen‐processing genes, PSMB8 and PSMB9, with vitiligo. Methods: In total 1320 cases of vitiligo (1050 generalized and 270 localized) and 752 healthy controls were studied for the PSMB9 exon 3 G/A single‐nucleotide polymorphism (SNP), PSMB8 exon 2 C/A SNP and PSMB8 intron 6 G/T SNP at site 37 360 using polymerase chain reaction (PCR)–restriction fragment length polymorphism. Real‐time PCR was used for transcriptional expression of PSMB8 and cytokines. Expression of ubiquitinated proteins and phosphorylated‐p38 (P‐p38) was studied by Western blotting. Results: Significant increases in PSMB8 exon 2 allele A ( P < 2.07 × 10 −6, odds ratio 1·93) and genotypes AA ( P < 1.03 × 10 −6, odds ratio 2·51) and AC ( P < 1.29 × 10 −6, odds ratio 1·63) were observed in patients with vitiligo. Interferon‐γ stimulation induced lower expression of PSMB8 in peripheral blood mononuclear cells of cases compared with controls, suggesting impaired antigen processing, which was confirmed by accumulation of ubiquitinated proteins in both lesional and nonlesional skin of patients with vitiligo. Expression of proinflammatory cytokines – interleukin (IL)‐6, IL‐1β and IL‐8 – was higher in the lesional skin. P‐p38 expression was variable but correlated with the amount of ubiquitinated proteins in the lesional and nonlesional skin, suggesting that the inflammatory cytokine responses in lesional skin could be a result of both P‐p38‐dependent and ‐independent pathways. Conclusions: The PSMB8 exon 2 SNP is significantly associated with vitiligo. Accumulation of ubiquitinated proteins in skin of cases of vitiligo suggests their aberrant processing, which may promote the development of the disease. Abstract : What's already known about this topic? Antigen presentation is a hallmark of autoimmune disorders like vitiligo. Peptides presented to CD8 + cytotoxic T cells by major histocompatibility complex class I molecules are generated from ubiquitin‐tagged cytosolic proteins, degraded by a multicatalytic, cytosolic immunoproteasome complex encoded by the PSMB9 and PSMB8 genes. Single‐nucleotide polymorphisms (SNPs) in these genes may be involved in their differential expression and function, which may be detrimental for manifestation of vitiligo. What does this study add? This study highlights a significant role of PSMB8 SNPs in manifestation of vitiligo through aberrant processing of self‐antigens and accumulation of ubiquitinated proteins in the lesional and nonlesional epidermis of vitiligo. Reduced expression of PSMB8 in vitiligo peripheral blood mononuclear cells after interferon‐γ stimulation suggests its role in inducing inflammatory responses, probably through accumulation of ubiquitinated proteins leading to reactive oxygen species production and autoinflammatory immune responses. What is the translational message? Strategies to clear the accumulation of ubiquitinated proteins from the skin may result in reduced inflammation. Identification of molecules that could target the altered turnover of ubiquitinated proteins may help in designing immunotherapeutic approaches for treatment of vitiligo. Respond to this article